Prediction of Ultimate Lateral Capacity of Rigid Spiral Pile under Static Loading in Cohesionless soil - Amarbayar Jugdernamjil; Noriyuki Yasufuku; Adel Alowaisy (Lowland Technology International, 2021)
1g model test is carried out to evaluate the ultimate lateral capacity of the spiral model pile in dense and medium dense cohesionless soil. The spiral model pile is scaled down using a proper similarity equation considering the equivalent second moment of area. The equivalent second moment of the area was obtained from a four-point bending test on a flat bar and compared with a spiral bar. In order to identify the lateral capacity of the spiral model pile, the conventional pipe and flat bar model piles were conducted as well. Winkler's model was adopted to predict the rigid spiral pile's ultimate lateral capacity in cohesionless soil. A simplified model is proposed by developing ultimate lateral soil pressure. The novel shape factor for spiral was obtained for the evaluation of ultimate lateral soil pressure by considering the projected area of the pile. The projected area of the spiral pile was compared with the pipe pile. The comparison study was conducted to spiral, flat, bar, and pipe pile, respectively, for inspecting accuracy. Among the comparison, the proposed model was indicated as a more accurate model than others. The spiral pile was shown a similar performance with a flat bar in both the empirical and the experimental results.